STRATEGI PENGEMBANGAN EKOWISATA TELAGA BIRU OPERSNONDI KAMPUNG SEPSE, DISTRIK BIAK TIMUR, KABUPATEN BIAK NUMFOR - Worabay, Yanke Elzirra T.; Fatem, Sepus Marten; Peday, Mariana H; Marwa, Jonni; Morimuzendy, Agustina S (Universitas Lambung Mangkurat, 2023)
This study aims to find out the development strategy of Blue Lake Opersnondi Ecotourism in Sepse Village, East Biak District Biak Numfor Regency. This study used a descriptive method using data collection techniques with field observations, interviews, and literature studies. The data analysis used in this study is the Strength, Weakness, Opportunity, and Threats (SWOT) analysis. The results of this study show that f Strength actors are the largest indicators, where the total weight value is 2,31, the Weakness factor with a total weight value of 2,21, Opportunity factors with a total weight value of 2,64, and Factor Acaman with a total weight value of 1,79. From the results of the grand matrix of strategies that have been obtained, the development of the blue lake tourist attraction opersnondi is in kuadran I, which is in the category of aggressive strategies, which weighs the factor Strength and Opportunity to make up the largest total weight value. The results of interviews from the sespse village community and also stakeholders related to the development of blue lake tourist attractions strongly agree on the development of blue lake tourist attractions opersnondi and the community are actively involved.